Highly flexible and stretchable strain sensors based on conductive whisker carbon nanotube films - Zhang, Jinling; Wang, Min; Yang, Zhaohui; Zhang, Xiaohua (Carbon (New York), 2021)
We fabricated a conductive whisker carbon nanotube (CNT) film by a simplified Langmuir−Blodgett method in which loose whisker CNTs (WCNTs) were densified via a capillary-induced compression assisted by a porous sponge. After this densification treatment, WCNTs formed conductive networks. The deformation of WCNT networks can cause a significant resistance change. The electric resistance of conductive WCNT network is highly sensitive to external mechanical stimuli. We developed a flexible and stretchable WCNT-based strain sensor using WCNT film sandwiched between two pieces of elastic polydimethylsiloxane films. This WCNT-based sensor exhibits an extremely high sensitivity (up to a gauge factor of 4839) over a wide strain range, fast response (60 ms), the good stability of mechanical cycling (1000 cycles), and extremely wide response window (it can detect strains as low as 0.05% and up to 420%). The WCNT-based sensing devices are able to monitor human muscle activity ranging from vital signs to high-strain human joint motions due to their high sensitivity and wide strain sensing range. [Display omitted]